Analysis of three genetic polymorphisms in Malaysian essential hypertensive and type 2 diabetic subjects - Vasudevan, Ramachandran; Ismail, Patimah; Stanslas, Johnson; Shamsudin, Norashikin (Academic Journals, 2009)
Genetic polymorphisms were associated with an increase in the risk of developing disease and they are integral to the development of genetic marker to identify the individuals at risk. The genotypic distribution of various genetic polymorphisms involved in essential hypertension (EHT) and type 2 diabetes mellitus (T2DM) in Malaysian subjects has not been well characterized. The main objective of this study was to determine the association of S477X polymorphism of LPL gene, A6244G polymorphism of IRS-1 gene and C825T polymorphism of GN3 gene with EHT and T2DM in Malaysian subjects. This study includes 70 EHT, 60 T2DM, 65 EHT with T2DM and 75 control subjects. Genotyping of all the three polymorphisms was performed by PCR-RFLP method with the respective primers and restriction enzymes. The genotypic and allelic frequencies of the respective polymorphisms of the genes did not differ significantly (p>0.05) with EHT and T2DM in Malaysian subjects. The results of this study suggested that, S477X genotypes of LPL gene, A6244G genotypes of IRS-1 gene and C825T genotypes of GN3 gene was not associated with EHT and T2DM in Malaysian subjects.